The Development of Assessment Instruments in Improving Analysis Thinking Ability - Sihotang, Ijah Mulyani; Fatmawarni, Fatmawarni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to improve analytical thinking skills and student accounting learning outcomes through the development of assessment instruments. The object of this research is journal material. This research is a development research that develops an assessment instrument adopting the Thiagarajan development model. Data collection techniques with tests and observations. The data analysis technique of this research is descriptive qualitative analysis technique. The assessment instrument designed was tested for validity and reliability. The test instrument test that is designed is valid and feasible to use and the Test Reliability test is declared reliable. The ability to think in analyzing students through journals can be categorized as low, this can be seen from the average score of 37.66.